Drug Dosing Rationality Based on Jelliffe Equation in Acute Kidney Injury - Dealinda Husnasya; Mawardi Ihsan (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Patients with Acute Kidney Injury (AKI) experience changes in unstable kidney function which is characterized by instability of serum creatinine values that affect the concentration of drugs in the body. Therefore, adjusting the dosage and frequency of the drug is an important concern. This study aimed to determine the proportion of rational drug dosage regimens in hospitalized patients with AKI. This research was a retrospective observation study with cross sectional design. Sample collection was carried out using simple random sampling method for patients who were hospitalized with AKI during January 1st till December 31, 2017. Data analysis was carried out descriptively to see the proportion and description of the rationality of each dosage regimen given to patients. This research was conducted at the dr. Sardjito General Hospital Yogyakarta. The results showed that the proportion of rational drug dosage regimens given to 100 inpatients with AKI was 60.00% based on literature and 94.12% based on predictive steady-state concentration calculation. Irrationality of the dosing regimen because of administration interval was 52.84%; because of dose was 17.05%; and because of both were 30.11%. The irrationality based on predictive steady concentration showed that drug concentration below minimum effective concentration was 33.33% and over minimum toxic concentration was 66.67%. The proportion of rational drug dosage regimens given to 100 inpatients with AKI based on literature and calculation of predictive steady-state concentrations were quite high. However, some dosing regimens were still irrationally prescribed with the irrationality form were generally in the form of irrational delivery interval with excessive drug concentration.